Sclerotinia sclerotiorum virulence is affected by mycelial age via reduction in oxalate biosynthesis - Ji-peng WANG; You-ping XU; Xian-peng ZANG; Shuang-sheng LI; Xin-zhong CAI (Journal of Integrative Agriculture, 2016)
Sclerotinia sclerotiorum is one of the most devastating necrotrophic phytopathogens. Virulence of the hyphae of this fungus at different ages varies significantly. Molecular mechanisms underlying this functional distinction are largely unknown. In this study, we confirmed the effect of mycelial culture time/age on virulence in two host plants and elucidated its molecular and morphological basis. The virulence of the S. sclerotiorum mycelia in plants dramatically decreases along with the increase of the mycelial age. Three-day-old mycelia lost the virulence in plants. Comparative proteomics analyses revealed that metabolism pathways were comprehensively reprogrammed to suppress the oxalic acid (OA) accumulation in old mycelia. The oxaloacetate acetylhydrolase (OAH), which catalyzes OA biosynthesis, was identified in the S. sclerotiorum genome. Both gene expression and protein accumulation of OAH in old mycelia were strongly repressed. Moreover, in planta OA accumulation was strikingly reduced in old mycelia-inoculated plants compared with young vegetative mycelia-inoculated plants. Furthermore, supply with 10 mmol L−1 OA enabled the old mycelia infect the host plants, demonstrating that loss of virulence of old mycelia is mainly caused by being unable to accumulate OA. Additionally, aerial mycelia started to develop from 0.5-day-old vegetative mycelia and dominated over 1-day-old mycelia grown on potato dextrose agar plates. They were much smaller in hypha diameter and grew significantly slower than young vegetative mycelia when subcultured, which did not maintain to progenies. Collectively, our results reveal that S. sclerotiorum aerial hyphae-dominant old mycelia fail to accumulate OA and thereby lose the virulence in host plants.